ANALISIS KINERJA DAN PROYEKSI BISNIS PT. BPR RAMBI ARTHA PUTRA - Febri Ariyanti Ningsih (Relawan Jurnal Indonesia, 2020)
BPR RAMBI ARTHA PUTRA is a BPR engaged in banking, owned by the private sector. The problems faced by BPR need a solution. Thus, the problem formulation of this study is how the financial performance of rural banks using horizontal analysis, vertical analysis and financial ratios. The method used in this study is a quantitative method. The analysis technique used is descriptive analysis, horizontal analysis, vertical analysis and financial ratio analysis. The results of the vertical analysis can be concluded that the vertical analysis of the 2015-2018 balance report, Asset from year to year has increased, Liabilities have also increased significantly. The results of the horizontal analysis can be concluded that the assets from 2015 to 2019 in the June period increased from year to year. The June period Loans granted to customers were the biggest factor (first) in the increase in the number of assets, the second was cash and equivalents. with cash. In the element of liabilities, a significant factor is influenced by loans, whereas in equity there is no additional capital, but there are additional reserves which the amount continues to increase per year but is not significant. The results of the ratio analysis show that the financial condition of PT. BPR RAMBI ARTHA PUTRA is in good health and, from year to year, has a good trend